(untitled) (Regional aspects of productive forces development of Ukraine, 2020)
Introduction. In the context of exacerbation of the crisis in the world economy, it is becoming increasingly important to study the experience of public policy in key sectors of the economy, including tourism, which are able to ensure economic growth in the country. There is a growing attention to the practice of creation and functioning of tourism regulation institutions, which makes it possible to identify the main priority measures in certain socio-economic and political conditions of development. Goal. To analyze modern models of state regulation of tourism and on the basis of consideration of their classifications carried out by Ukrainian scientists, to determine the best option that should be used in post COVID-19 conditions in Ukraine. Methods. The article uses logical-abstract, comparative and methods of analysis and synthesis in the study of modern models of state regulation of tourism, defined goals and conclusions. Results. The author explores four main models of state regulation of tourism. The peculiarity of the American model is the absence of a central government institution responsible for the functioning and development of tourism. The centralized model provides for state regulation of tourism by a separate – central executive body at the ministry level. The European model is that the regulation of tourism is carried out at the level of a multi-sectoral ministry, within which a special structural unit operates. The mixed model of state regulation of tourism envisages the creation of a combined ministry, which, along with the regulation of tourism, will take care of issues of economic and social spheres of the state that are related to tourism (culture, sports, etc.). The expediency of using a centralized model of state regulation of tourism in Ukraine is substantiated. Conclusions. The analysis of world models of state regulation of tourism allowed to substantiate expediency to use in Ukraine the model of centralized state regulation of tourism which, in our opinion, in modern realities of development of the Ukrainian state will provide (using foreign experience) the decision of problems of development of domestic tourism. its management system, the level of logistics, the role of state and public institutions, the effectiveness of economic and legal regulation.